2006
DOI: 10.1021/ja065477a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Control of Unwinding and Rewinding of a Double Helix of Oligoresorcinol Using Cyclodextrin/Adamantane System

Abstract: The double helix of the oligoresorcinol nonamer formed in water was unwound by beta-cyclodextrin (beta-CD), and the resulting single strands of the nonamer threaded the beta-CD to form a twisted [3]-pseudorotaxane with a controlled helicity. Upon the addition of an adamantane, the single strand of the oligoresorcinol nonamer was expelled out of the beta-CD wheels, thus regenerating the double helix. This supramolecularly controlled, reversible unwinding and rewinding of the double helix is unique and can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 20 publications
0
46
0
1
Order By: Relevance
“…[9] As a result, considerable advancement has been achieved not only in secondary structures, but also in intrinsic properties such as recognition, chiral amplification, catalysis, and molecular machines triggered by acid/base, light, and the environment. [10] In view of the fact that the tertiary structures are widely adopted by biomacromolecules like proteins, in which multiple helices associate reciprocally to create a platform to perform various functions such as catalysis and recognition, chemists are motivated to assemble these available foldamers into higher-order structures, that is, tertiary structures. [11] For example, Huc et al, [11d] reported that the abiotic proteomorphous foldamer exhibited a tertiary structure like a small protein.…”
Section: Introductionmentioning
confidence: 99%
“…[9] As a result, considerable advancement has been achieved not only in secondary structures, but also in intrinsic properties such as recognition, chiral amplification, catalysis, and molecular machines triggered by acid/base, light, and the environment. [10] In view of the fact that the tertiary structures are widely adopted by biomacromolecules like proteins, in which multiple helices associate reciprocally to create a platform to perform various functions such as catalysis and recognition, chemists are motivated to assemble these available foldamers into higher-order structures, that is, tertiary structures. [11] For example, Huc et al, [11d] reported that the abiotic proteomorphous foldamer exhibited a tertiary structure like a small protein.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic oligosaccharides such as b-or g-cyclodextrin (CyD) readily unwound the double helical 7 and formed [3]pseudorotaxane that consisted of one strand of the oligoresorcinol and two CyD wheels. [46] The [3]pseudorotaxanes showed a twist-sense bias induced by the chirality of the CyDs, as evidenced by the significant induced CDs, hyperchromicity of the absorption spectra, and drastic 1 H NMR spectral changes. Upon the addition of an adamantane derivative with a high affinity toward b-CyD, the [3]pseudorotaxane with b-CyD reverted to the double helix, forming an inclusion complex of b-CyD with the adamantane.…”
Section: Resultsmentioning
confidence: 99%
“…Wir möchten hier nur sehr knapp eine Auswahl nennen und verweisen den Leser für weitere Informationen auf die angegebenen Referenzen. Von anderen Forschungsgruppen untersuchte dynamische Bewegungssysteme und/oder Konformationsänderungen umfassen: 1) das helikale Umwickeln von Quinquepyridin, Bishydrazonen, Pentaoxyethylen sowie anderen Liganden um Metallionen; 2) Bewegungsprozesse, Schalter, Metallkomplexe und Sensoren auf Basis von Hydrazonen;, 3) Faltung‐Entfaltung eines Terpyridin‐Komplexes; 4) die Ausweitung von helikalen Molekülen durch die Bildung von doppelhelikalen Dimeren; 5) das lösungsmittelinduzierte oder Chaperon‐assistierte Falten und Entfalten oder pH‐modulierte Schalter in helikalen Strängen (Änderung der helikalen Steigung); 6) eine sprungfederartige Bewegung (partielles Entfalten und Änderung der Helix‐Gangweite; 7) eine temperaturkontrollierte Steigerung der Helix‐Laufweite; 8) Metallionen‐assistierte Prozesse; 9) eine oligomere o ‐Phenylenhelix, die dynamische Bewegung als Reaktion auf eine Änderung des Redoxzustands eingeht; 10) reversibles Abwickeln einer Oligo‐Resorcinol‐Doppelhelix; 11) das Falten und Entfalten von Poly(ethylenglycol) und Poly(ethylenimin) in Lösung; 12) das anioneninduzierte Falten von aromatischen Amid‐basierten Oligomeren; 13) das konformative Schalten von phenolischen Oligoamiden (linear zu gebogen); 14) photoschaltbare Foldamere;, 15) das säureinduzierte molekulare Falten und Entfalten von Pyrimidin‐Amid‐basierten Oligomeren; 16) das durch Komplexierung induzierte Entfalten von heterocyclischen Harnstoffderivaten; 17) das Falten/Entfalten von elektrochemisch adressierbaren Molekülen; 18) das lösungsmittelabhängige Falten/Entfalten von oligomeren Cholaten oder Foldameren; 19) das reversible Entfalten einer Helix einschließlich Depolymerisierung; 20) das stimulierte Falten und Entfalten von Polymeren; 21) das per pH‐Wert adressierbare Umwickeln oder Falten/Entfalten von DNA i‐Motiven; 22) die lösungsmittelinduzierte Konformationsänderung von Poly( m ‐ethinylpyridinen); 23) die akkordeonartige Oszillation von Helices oder molekularen Sprungfedern; und 24) die hydrazonbasierten zwei‐ und mehrkernigen Komplexe (oft erzeugt durch Entwindung von gebogenen Liganden) . Übersichtsartikel zu abstimmbaren helikalen Strukturen und die funktionelle ...…”
Section: Einführungunclassified